O tempo de viagem da população rural aos serviços de saúde mapeado em sistemas de informação geográfica (SIG) - Ferreira, Ricardo Vicente; Raffo, Jorge Gustavo da Graca (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2014)
Distance and travel time are important parameters in the evaluation of access to health services, especially for the population living in the countryside. In the present work, a GIS-based methodology is developed for the mapping of rural road networks and the determination of travel impedances in order to optimize the travel time of the rural population to health care facilities. Data on rural roads classes, slope, sinuosity, visibility and land use are considered in the composition of the impedances synthesis and its application on car travel time. The methodology was applied to the region of Registro (SP), and the results indicate an unequal distribution of health services.